# MATH133_U4_answer - g(x)= 2x/x-3 2x/x-3 (x-3)=0 x=3 x ≠ 3...

This preview shows pages 1–3. Sign up to view the full content.

Student Answer Form Unit 4 1. a. j(x)=(x+1)^2+3 y=(x+1)^2+3 No x-intercept Y = 4 Y = (1)^2 + 3 Y= (1) + 3 Y = 4 The graph of f(x) shifted 3 units to the left. b. f(x)=x^2 h (x) = x^2 -2 x= sqrt2 – sqrt2 (0) y = -2 x^2 – 2 = 0 x^2= 2 x = ± sqrt2 x= sqrt2, sqrt-2 y = (0)^2 – 2 y = 0- 2 y = -2 The graph of f(x) shifted 2 units down. c .i (x) = (x+3)^2 Y = (x + 3)^2 X = - 3 Y = 9 (x+#)^2 = (0) X= -3 Y = (0 +3)^2 Y = (3) ^2 Y = 9 The graph of f(x) shifted 3 units up. d. f(x) = x^2 g(x)= (x-2)^2 x=2, y=4 (x-2)^2= 0 X = 2 Y = (0 -2)^2 Y = (-2) ^2 Y = 4

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
The graph of f(x) shifted 2 units to the right. 2. a. f(x)= 4x^2 – 7x + 3(all real numbers) There is no real number that makes the expression undefined. b. g(x)=10/x+7 10/x+7 (x+7)=0 x 7 x -7 (- ,-7) (-7, ) c. f(x) = sqrt 4x – 16 sqrt 4(x) + 4 (-4) sqrt 4 (x-4) (x-4) < 0 x < 4 x 4 [4, ) d.
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: g(x)= 2x/x-3 2x/x-3 (x-3)=0 x=3 x ≠ 3 (-∞ , 3) ∪ (3, ∞ ) e. f(x)=3x-9 ( all real numbers) There is no real numbers that makes this expression undefined. 3. a. f (x) = 4/x+5 (x+5)=0 x= - 5 x ≠-5 x = (-∞ , - 5) ∪ (-5, ∞ ) b. g(x) =5x^2 – 4/ x + 1 lim 5x^2 – 4/x + 1 x + 1 5x -5/ sqrt 5x^2 + 0x -4-5x^2 – 5x-5x -4 5x + 5 = 1 5x -5 + 1/x + 1 Y = 5x – 5 Y= -∞ c. f (x) = 3x -1/x + 4 (x+4) = 0 X = - 4 X ≠-4 (-∞ , -4) Y= 3 X + 4 sqrt 3/ 3x – 1-3x – 12- 13 3- 13/ x + 4 d. g(x) = x + 7/ x^2 -4 g(x) = x+7/ (x-2) (x+2) (x-2) (x+2)= 0 x=2, -2 x ≠ , ≠ -2 x 2 (-∞, - ) ∪ (- , )∪ ( ,∞) 2 2 2 2 + / ( - ) ( + ) Lim x 7 x 2 x 2 = Y + - + X^2 0x 4 sqrt x 7 + / – X 7 x ^2 4 X= Y = 0...
View Full Document

## This note was uploaded on 05/21/2011 for the course MATH 133 taught by Professor Hutchins during the Winter '10 term at AIU Online.

### Page1 / 3

MATH133_U4_answer - g(x)= 2x/x-3 2x/x-3 (x-3)=0 x=3 x ≠ 3...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online